An overview of civil procedure in Argentina - Verbic, Francisco (Civil Procedure Review, 2019)
The paper presents an overview of Federal Civil Procedure in Argentina, analyzing its historical and cultural influences as well as current trends. Firstly, it describes how the Spanish conquest influenced Argentine civil procedure and the main reforms that took place during 1968, 1981 and 2001. Then, it describes Argentine civil procedure main features, such as the “attenuated party-driven procedure”, the “contradiction principle”, and the “mixed written-oral system”, among others. Particularly, it focuses on two procedural devices developed along the last twenty-five years: mandatory mediation before accessing to courts and class actions litigation. Finally, the report states that, despite Argentina´s reform efforts, the Federal Civil Procedure structure still works with an outdated model based in a written scheme, with low levels of transparency and publicity, no close contact between parties and judges and lacks of new technologies, among other structural problems.